Clinical and Demographic Features of Pseudotumor Cerebri Syndrome Diagnosed in a University Hospital - Demet Arslan; Adalet Arıkanoğlu; Eşref Akıl (Türk Nöroloji Dergisi, 2017)
Objective: Pseudotumor cerebri syndrome (PTCS) is characterized by symptoms and signs of increased intracranial pressure without ventriculomegaly, intracranial tumor or mass. This study aimed to explore and analyze 34 patients with PTCS according to age, sex, symptoms of the disorder, cranial magnetic resonance images findings, etiology, and treatment. Materials and Methods: A total of 34 patients who were diagnosed as having PTCS and followed up between January 2011 and August 2016 by Dicle University Medical School Neurology Department were included in this study. PTCS was diagnosed in accordance with the modified Dandy criteria. Results: Thirty-four patients were identified as having PTCS. Twenty-one (91.2%) had headache, 19 (55.9%) had blurred vision, 6 (17.6%) had diplopia, 2 (5.9%) had vertigo, 1 (2.9%) had tinnitus, and 1 (2.9%) had numbness of the face. Twenty-seven patients were diagnosed as having idiopathic intracranial hypertension, 21 (61.8%) had no etiologic factors. Six (17.6%) patients were obese, one of whom had recently gained weight and another had polycystic ovary syndrome. Seven patients were thought to have secondary PTCS with the following etiologic factors: 2 (5.9%) patients had Hashimoto’s thyroiditis, 1 (2.9%) had a history of all-trans retinoic acid intake due to a malignancy, 1 (2.9%) had choroid plexus granuloma, 2 (5.9%) had sinus venous thrombosis, and 1 (2.9%) had Familial Meditteranian Fever. Conclusion: Although PTCS was described many years ago, its physiopathology and exact treatment procedures are not clearly understood. The most important target of its treatment is to prevent loss of vision and improve symptoms. With a better understanding of its pathophysiology, effective treatment protocols will be developed